2017
DOI: 10.1038/srep41475
|View full text |Cite
|
Sign up to set email alerts
|

Fewer clouds in the Mediterranean: consistency of observations and climate simulations

Abstract: Clouds play a major role in the climate system, but large uncertainties remain about their decadal variations. Here we report a widespread decrease in cloud cover since the 1970 s over the Mediterranean region, in particular during the 1970 s–1980 s, especially in the central and eastern areas and during springtime. Confidence in these findings is high due to the good agreement between the interannual variations of cloud cover provided by surface observations and several satellite-derived and reanalysis produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 61 publications
(77 reference statements)
5
38
1
Order By: Relevance
“…Also, in some previous studies the dimming period observed between the 1950s and 1980s was mainly attributed to cloud changes instead of direct aerosol effects (Liepert, ). Stjern et al () and Parding et al () also found that changes in clouds are the main reason for trends in SSR in northern Europe, and in the Mediterranean observations indicate fewer clouds for the period 1971 to 2005 (Sanchez‐Lorenzo et al, ). In the United States, observed positive trends in SSR since the 1990s are also mainly attributed to changes in cloud cover (Augustine & Dutton, ).…”
Section: Discussionmentioning
confidence: 94%
“…Also, in some previous studies the dimming period observed between the 1950s and 1980s was mainly attributed to cloud changes instead of direct aerosol effects (Liepert, ). Stjern et al () and Parding et al () also found that changes in clouds are the main reason for trends in SSR in northern Europe, and in the Mediterranean observations indicate fewer clouds for the period 1971 to 2005 (Sanchez‐Lorenzo et al, ). In the United States, observed positive trends in SSR since the 1990s are also mainly attributed to changes in cloud cover (Augustine & Dutton, ).…”
Section: Discussionmentioning
confidence: 94%
“…New dynamic thresholds for infrared-brightness temperature-difference features have been introduced, in particular for the differences relative to the 3.7 micron channel over arid and semi-arid regions. For CLARA-A1 some static thresholds were used previously which led to occasional false cloudiness and unrealistic cloud distributions and trends over semi-arid regions, as reported by Sun et al (2015) and Sanchez-Lorenzo et al (2017). The new thresholds are functions of surface emissivity (from MODIS climatologies) and viewing angles.…”
Section: Cloud Productsmentioning
confidence: 99%
“…On the other hand, 10 there are studies arguing that these changes in SSR, especially in pristine or remote areas, were mainly driven by natural changes in cloud cover and/or cloud properties (Dutton et al, 2006;Long et al, 2009;Augustine and Dutton, 2013;Stanhill et al, 2014). However for Europe, several studies have reported either no statistically significant trends in cloud cover since 1990 or no strong evidence that changes in cloud cover were mainly responsible for the observed SSR trends (Norris and Wild, 2007;Sanchez-Lorenzo et al, 2009, 2012, 2017aVetter and Wechsung, 2015). Furthermore, other studies that 15 focused on Europe pointed to aerosols, and especially the direct effect, as the main driver for the brightening since the mid1980s (Ruckstuhl et al, 2008(Ruckstuhl et al, , 2010Ruckstuhl and Norris, 2009;Folini and Wild, 2011;Wang et al, 2012b;Cherian et al, 2014;Nabat et al, 2014;Turnock et al, 2015;Manara et al, 2016).…”
Section: Introductionmentioning
confidence: 94%